The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1074/jbc.m114.635730
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-suppressive p53 Signaling Empowers Metastatic Inhibitor KLF17-dependent Transcription to Overcome Tumorigenesis in Non-small Cell Lung Cancer

Abstract: Background: How Krüppel-like factor 17 (KLF17) controls metastasis and epithelial-mesenchymal transition (EMT) during cancer progression remains unknown. Results: Tumor-suppressive p53 signaling is critical for KLF17 to inhibit cancer metastasis in NSCLC. Conclusion:These results indicate novel insights into the anti-EMT effect of KLF17 via p53-dependent pathway. Significance: Targeting KLF17 for cancer therapy may be applicable to NSCLC tumors with TP53 status, which may improve the prognosis of NSCLC patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…With the advances of oncological researches, many critical oncogenes or tumor suppressors in NSCLC were identified, such as p53, EGFR, PD-1/ PD-L1 [29][30][31]. Several molecular targeted therapies have been developed, such as EGFR-tyrosine kinase inhibitor and PD-1/PD-L1 antibodies [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…With the advances of oncological researches, many critical oncogenes or tumor suppressors in NSCLC were identified, such as p53, EGFR, PD-1/ PD-L1 [29][30][31]. Several molecular targeted therapies have been developed, such as EGFR-tyrosine kinase inhibitor and PD-1/PD-L1 antibodies [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Further evidence in non-small-cell lung cancer also suggests that KLF17 could function as a tumor suppressor [177]. These studies suggested that p53 recruits p300 to the KLF17 promoter to acetylate and turn on transcription [177].…”
Section: Krüppel-like Factor 17mentioning
confidence: 97%
“…These studies suggested that p53 recruits p300 to the KLF17 promoter to acetylate and turn on transcription [177]. In addition, p53 also physically interacts with KLF17 and promotes binding of KLF17 to certain gene promoters and promotes transcription of p53, p21, and pRB [177]. These data suggest an intricate cross-talk between KLF17 and p53 in tumorigenesis.…”
Section: Krüppel-like Factor 17mentioning
confidence: 97%
See 1 more Smart Citation
“…Krüppel-like factors are highly conserved zinc finger transcription factors that serve as key regulators of critical biological cellular processes, including cell proliferation, differentiation, apoptosis, and migration [9,10]. Many studies that have focused on the function of KLF17 in tumorigenesis have reported that KLF17 plays a vital role in cancer development [11][12][13].…”
Section: Introductionmentioning
confidence: 99%